(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article presents a detailed analysis of the factors determining the mechanical and biological properties of polymer-matrix biocomposites. The performance of these materials depends not on a single parameter, but on a complex set of interrelated characteristics, including the type of polymer matrix, the nature of the filler, its particle size and distribution, the quality of interfacial adhesion, the porous architecture of the material, and its degradation behavior over time. A comparative assessment was carried out for systems based on PLA, PCL, and PEEK, as well as for composites containing hydroxyapatite, β-tricalcium phosphate, collagen, or cellulose fibers. For bone tissue engineering, the most important properties are stiffness (elastic modulus), compressive strength, osteoconductivity, and structural stability. For materials intended for soft tissue engineering, greater importance is attached to elasticity, surface hydrophilicity, and the ability to promote cell adhesion. It is concluded that purposeful control of the composition and internal structure of a biocomposite makes it possible to achieve the required balance between mechanical strength, biocompatibility, and controlled degradability.